Dari Informasi ke Donasi: Bagaimana Konten di Media Sosial Mempengaruhi Niat Donasi di Platform Amal Online? Peranan Rasa Syukur Sebagai Moderasi - Intan Purnama Sari; Ferry Tema Atmaja (JWM (JURNAL WAWASAN MANAJEMEN), 2026)
Advances in digital technology have revolutionized the world of philanthropy, driving the rapid growth of online donations in Indonesia. This study aims to understand the influence of information content on social media on one's intention to donate through online fundraising platforms, while also examining the role of generosity as a mediating variable and gratitude as a moderating variable in this relationship. This study employs a quantitative approach, collecting data from 300 respondents via an online questionnaire using the T-Survey platform. The data are analyzed using the Structural Equation Modeling (SEM) method, aided by SmartPLS 4.1 software. The results showed that information content positively and significantly affects charity donation intention. In addition, information content also significantly affects generosity, which in turn impacts increasing donation intentions. Other findings show that gratitude positively and significantly strengthens the influence of information content on donation intentions. This study makes a theoretical contribution to the literature on digital donation behavior and offers practical implications for nonprofit organizations in designing effective communication strategies through social media.